Comparison of the gut microbiota composition between wild and captive sika deer (Cervus nippon hortulorum) from feces by high-throughput sequencing. (December 2017) - Guan, Yu; Yang, Haitao; Han, Siyu; Feng, Limin; Wang, Tianming; Ge, Jianping
Abstract The gut microbiota is characterized as a complex ecosystem that has effects on health and diseases of host with the interactions of many other factors together. Sika deer is the national level for the protection of wild animals in China. The available sequencing data of gut microbiota from feces of wild sika deer, especially forCervus nippon hortulorum in Northeast China, are limited. Here, we characterized the gastrointestinal bacterial communities of wild (7 samples) and captive (12 samples) sika deer from feces, and compared their gut microbiota by analyzing the V3–V4 region of 16S rRNA gene using high-throughput sequencing technology on the Illumina Hiseq platform.Firmicutes (77.624%), Bacteroidetes (18.288%) andTenericutes (1.342%) were the most predominant phyla in wild sika deer. While in captive sika deer, Firmicutes (50.710%) was the dominant phylum, followed byBacteroidetes (31.996%) andProteobacteria (4.806%). A total of 9 major phyla, 22 families and 30 genera among gastrointestinal bacterial communities showed significant differences between wild and captive sika deer. The specific function and mechanism ofTenericutes in wild sika deer need further study. Our results indicated that captive sika deer in farm had higher fecal bacterial diversity than the wild. Abundance and quantity of diet source for sika deer played crucial role in shaping the composition and structure of gut microbiota.